Pectin obtention from agroindustrial wastes of Malus domestica using green solvents (citric acid and natural deep eutectic solvents). Chemical, thermal, and rheological characterization - Gómez Vargas, Carolina; Ponce, Nora Marta Andrea; Stortz, Carlos A.; Fissore, Eliana Noemi; Bonelli, Pablo; Otálora González, Carlos Mauricio; Gerschenson, Lía Noemí (Frontiers in Chemistry, 2025)
The use of green solvents, citric acid (CA), and natural deep eutectic solvents (NADES) for the obtention of pectin from wastes (pulp and peel) of Malus domestica was studied. The NADES used comprised citric acid–glucose–water (N1) or lactic acid–glucose–water (N2). The fractions rich in pectin obtained after exposure to NADES showed lower yield (≈4 g/100 g CA vs. ≈ 11 g/100 g CA), equal to or lower degree of methoxylation (53–71 mol/100 mol CA vs. 73 mol/100 mol CA), equal to or greater content of uronic acid (50–63 g/100 g CA vs. 51 g/100 g CA) than those isolated with CA, and the ones obtained from peel were the most thermally stable. These pectins showed greater linearity, shorter branch lengths, and lower arabinose content than those obtained with CA. The neutral sugars present in the highest concentration in all the isolated fractions were arabinose, xylose, galactose, and rhamnose. Glucose was also detected, probably due to contamination with starch. Their aqueous solutions showed pseudoplastic behavior. The effect of ultrasound assistance was preliminarily evaluated in the production of pectic fractions using N2, observing higher yields (13–18 g/100 g), in general, a higher concentration of uronic acid and a higher degree of methoxylation when compared with the extraction without US. They also showed greater arabinose content (less degradative treatment), lower glucose content (increased purity), and higher rhamnogalacturonan I (RG-I) content. It is known that RG-I is linked to pectin bioactivity and rheological behavior. The green solvent techniques assayed allowed obtaining fractions rich in uronic acid with different chemical, thermochemical, and rheological characteristics. In the case of isolation with NADES, the yield was low, but preliminary tests with ultrasound assistance showed that it is possible to overcome this limitation.